The virtual hand illusion is moderated by context-induced spatial reference frames - Zhang, Jing; Ma, Ke; Hommel, Bernhard (Frontiers in Psychology, 2015)
The tendency to perceive an artificial effector as part of one’s own body is known to depend on temporal criteria, like the synchrony between stimulus events informing about the effector. The role of spatial factors is less well understood. Rather than physical distance, which has been manipulated in previous studies, we investigated the role of relative, context-induced distance between the participant’s real hand and an artificial hand stimulated synchronously or asynchronously with the real hand. We replicated previously reported distance effects in a virtual reality setup: the perception of ownership increased with decreased distance, and the impact of synchrony was stronger for short distances. More importantly, we found that ownership perception and impact of synchrony were affected by previous distance: the same, medium distance between real and artificial hand induced more pronounced ownership after having experienced a far-distance condition than after a near-distance condition. This suggests that subjective, context-induced spatial reference frames contribute to ownership perception, which does not seem to fit with the idea of fixed spatial criteria and/or permanent body representations are the sole determinants of perceived body ownership.